Investigation of the electrochemical and thermal stability of an ionic liquid based Na 0.6 Co 0.1 Mn 0.9 O 2 /Na 2.55 V 6 O 16 sodium-ion full-cell - Do, Minh Phuong (2019)
Electrolytes based on non-flammable and electrochemically and thermally stable ionic liquids (ILs) are rendered promising alternatives to the conventionally applied organic electrolytes for lithium as well as sodium ion batteries (SIBs). In this study the electrochemical performance and thermal stability of a SIB full-cell containing an IL based electrolyte is evaluated and compared to a reference system employing a conventional organic electrolyte. Compatibility of the IL electrolyte with the electrode materials Na0.6Co0.1Mn0.9O2 (NMO) and Na2.55V6O16 (NVO) is assured by SIB half-cell studies. In NMO/NVO full-cells the IL electrolyte outperforms the organic electrolyte in terms of cycling stability and columbic efficiency, reaching a retention of 76% after 100 cycles. Studies at 75°C show that, in contrast to the system based on the organic electrolyte, the IL-based SIB is capable of operating at elevated temperatures. Further, for the first time the superior safety of an IL-based SIB full-cell over the organic analogue is proven using Accelerating Rate Calorimetry (ARC) underlining the benefits of the IL based electrolyte.